Analisis Yuridis Terhadap Putusan Mahkamah Konstitusi Mengenai Hak Waris Anak Diluar Nikah - Dika Ratu Marfu’atun; Santy Fitnawati WN; Nathasya Nathasya; Surya Rianto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The purpose of this study is to find out the inheritance status of children outside of marriage and the division of inherits based on MK decision No. 46/PUU-VIII-2010. The results of the study show that because the out-of-marriage child and his biological father have a blood relationship, the Constitutional Court's ruling can be regarded as reinforcing the status of the off-marital child to acquire the right of inheritance from his biologic father. MK Decision No. 46/Law-VIII-2010 only deals with civil relations and does not regulate the inheritance. Therefore, the decision does not specify how much inheritance children can acquire outside of marriage.